2011
DOI: 10.1159/000329335
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Severe Postpartum Hemorrhage

Abstract: Background/Aims: The purpose of this study was to determine the relationship between maternal characteristics and severe postpartum hemorrhage (PPH). Methods: Medical records of women who delivered at Duke University Hospital between 2001 and 2004 with an ICD-9 code for PPH were reviewed. Women with PPH who received blood component therapy (severe PPH) were selected as cases and compared with controls matched for age, parity and mode of delivery. Results: Among 12,476 deliveries, there were 109 women with seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 32 publications
3
35
0
1
Order By: Relevance
“…No previous study has specifically identified Black African ethnicity as an independent predictor,1619,48 possibly because of lack of adjustment for potential confounding variables 4952. The independent relationship between BMI and PPH concurs with prospective cohort studies,14,53 although retrospective and routine data reports are equivocal 5456. The 4% increase per BMI unit becomes substantial in higher obesity categories.…”
Section: Discussionmentioning
confidence: 60%
“…No previous study has specifically identified Black African ethnicity as an independent predictor,1619,48 possibly because of lack of adjustment for potential confounding variables 4952. The independent relationship between BMI and PPH concurs with prospective cohort studies,14,53 although retrospective and routine data reports are equivocal 5456. The 4% increase per BMI unit becomes substantial in higher obesity categories.…”
Section: Discussionmentioning
confidence: 60%
“…[8], [11], [19], [53] However the role of body mass index on PPH is not clear yet. [54] Another possible and not registered confounder is magnesium sulphate, since it could, hypothetically, increase blood loss by vasodilatation, a tocolytic effect predisposing to uterine atony, prolonged bleeding time through platelet activity inhibition and red cell deformity and it is used in the Netherlands for the management of (pre-) eclampsia (as prevention in severe PE women (defined as blood pressure ≥110 mmHg diastolic or ≥110 mmHg systolic or proteinuria ≥5 grams or the presence of symptoms prognostic for eclampsia) or as treatment in women with eclampsia). Rouse et al determined an increased risk for PPH in hypertensive disorders which disappeared after correction for magnesium sulphate.…”
Section: Discussionmentioning
confidence: 99%
“…Body Mass Index has been identified more recently as a possible cause of PPH (Fyfe et al, 2012); however, as with the traditionally accepted risk factors listed above, it may be that a raised BMI is not an independent risk factor when other confounding variables are controlled (Paglia et al, 2012).…”
Section: Risk Factors For Pphmentioning
confidence: 99%